Automated Online Playlist Generation System - Aleksandar Stojmenski; Ivan Chorbev; Dragan Mihajlov (Institute of Advanced Engineering and Science, 2013)
This paper presents an online playlist management system designed to provide easy and intuitive management of audio and video playlists. Playlists can be uploaded, combined, downloaded, but also created online and stored for listening. Sharing of playlists is also enabled. State of the art AJAX technologies have been used to developed a fast and intuitive user interface. Automatic online playlist generation based on recognizing local songs and automated Youtube searching and queuing is also part of the system.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.5667